Interdisciplinary Teaching and Collaboration in Higher Education: A Concept Whose Time Has Come - Anita Weinberg; Carol Harding (Washington University Journal of Law & Policy, 2004)
We begin this discussion with a brief overview of the history of interdisciplinary education, particularly as it relates to teaching in law schools. We then discuss the goals of interdisciplinary education, with an emphasis on the cognitive and social significance of interdisciplinary thinking for students, faculty, and professionals. Several organizing assumptions follow that guided and, in some cases, emerged from our interdisciplinary efforts over the last six years to develop an interdisciplinary agenda within our university. Next, we identify patterns in interdisciplinary higher education (based on our own experiences), as well as the challenges and rewards for faculty and students that accompany such patterns. Finally, we integrate students’ evaluative comments as we describe some lessons learned to this point in the ongoing process of developing interdisciplinary programs.
Keywords: Interdisciplinary approach in education; Law – Study & amp; teaching